20.8% Slot‐Die Coated MAPbI3 Perovskite Solar Cells by Optimal DMSO‐Content and Age of 2‐ME Based Precursor Inks. Issue 10 (25th January 2021) - Li, Jinzhao; Dagar, Janardan; Shargaieva, Oleksandra; Flatken, Marion A.; Köbler, Hans; Fenske, Markus; Schultz, Christof; Stegemann, Bert; Just, Justus; Többens, Daniel M.; Abate, Antonio; Munir, Rahim; et al.
Abstract: Solar cells incorporating metal‐halide perovskite (MHP) semiconductors are continuing to break efficiency records for solution‐processed solar cell devices. Scaling MHP‐based devices to larger area prototypes requires the development and optimization of scalable process technology and ink formulations that enable reproducible coating results. It is demonstrated that the power conversion efficiency (PCE) of small‐area methylammonium lead iodide (MAPbI3 ) devices, slot‐die coated from a 2‐methoxy‐ethanol (2‐ME) based ink with dimethyl‐sulfoxide (DMSO) used as an additive depends on the amount of DMSO and age of the ink formulation. When adding 12 mol% of DMSO, small‐area devices of high performance (20.8%) are achieved. The effect of DMSO content and age on the thin film morphology and device performance through in situ X‐ray diffraction and small‐angle X‐ray scattering experiments is rationalized. Adding a limited amount of DMSO prevents the formation of a crystalline intermediate phase related to MAPbI3 and 2‐ME (MAPbI3 ‐2‐ME) and induces the formation of the MAPbI3 perovskite phase. Higher DMSO content leads to the precipitation of the (DMSO)2 MA2 Pb3 I8 intermediate phase that negatively affects the thin‐film morphology. These results demonstrate that rational insights into the ink composition and process control are critical to enable reproducible large‐scale manufacturing of MHP‐based devices for commercial applications. Abstract : The addition of the correct amounts of dimethyl sulfoxide (DMSO) with 2‐methoxyethanol (2‐ME) perovskite precursor ink is a crucial step toward reproducible slot‐die coatings and highly efficient perovskite solar cells. Through observing the drying process of 2ME‐DMSO inks from in situ X‐ray diffraction experiments, it is demonstrated that 11.77 mol% DMSO favorably affects thin film growth.